Enhanced Drought Stress Tolerance by the Arbuscular Mycorrhizal Symbiosis in a Drought-Sensitive Maize Cultivar Is Related to a Broader and Differential Regulation of Host Plant Aquaporins than in a Drought-Tolerant Cultivar - Quiroga, Gabriela; Erice, Gorka; Aroca, Ricardo; Chaumont, François; Ruiz-Lozano, Juan M. (Frontiers in Plant Science, 2017)
The arbuscular mycorrhizal symbiosis (AM) has been shown to improve maize tolerance to different drought stress scenarios by regulating a wide range of host plants aquaporins. The objective of this study was to highlight the differences in aquaporin regulation by comparing the effects of the AM symbiosis on root aquaporin gene expression and plant physiology in two maize cultivars with contrasting drought sensitivity. This information would help to identify key aquaporin genes involved in the enhanced drought tolerance by the AM symbiosis. Results showed that when plants were subjected to drought stress the AM symbiosis induced a higher improvement of physiological parameters in drought-sensitive plants than in drought-tolerant plants. These include efficiency of photosystem II, membrane stability, accumulation of soluble sugars and plant biomass production. Thus, drought-sensitive plants obtained higher physiological benefit from the AM symbiosis. In addition, the genes ZmPIP1;1, ZmPIP1;3, ZmPIP1;4, ZmPIP1;6, ZmPIP2;2, ZmPIP2;4, ZmTIP1;1, and ZmTIP2;3 were down-regulated by the AM symbiosis in the drought-sensitive cultivar and only ZmTIP4;1 was up-regulated. In contrast, in the drought-tolerant cultivar only three of the studied aquaporin genes (ZmPIP1;6, ZmPIP2;2 and ZmTIP4;1) were regulated by the AM symbiosis, resulting induced. Results in the drought-sensitive cultivar are in line with the hypothesis that downregulation of aquaporins under water deprivation could be a way to minimize water loss, and the AM symbiosis could be helping the plant in this regulation. Indeed, during drought stress episodes, water conservation is critical for plant survival and productivity, and is achieved by an efficient uptake and stringently regulated water loss, in which aquaporins participate. Moreover, the broader and contrasting regulation of these aquaporins by the AM symbiosis in the drought-sensitive than the drought-tolerant cultivar suggests a role of these aquaporins in water homeostasis or in the transport of other solutes of physiological importance in both cultivars under drought stress conditions, which may be important for the AM-induced tolerance to drought stress.